2019
DOI: 10.3390/ani10010042
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Impacts of Different Omega-6 to Omega-3 Fatty Acid Ratios in Corn–Soybean Meal-Based Diet on Growth Performance, Nutrient Digestibility, Blood Profiles, Fecal Microbial, and Gas Emission in Growing Pigs

Abstract: This study was conducted to evaluate the effect of different omega-6: omega-3 fatty acid (FA) ratios in a corn–soybean meal-based diet in growing pigs. A total of 140 [Duroc × (Landrace × Yorkshire)] growing pigs with an average body weight (BW) of 24.75 ± 1.43 kg were used in a 6-week trial. Pigs were allocated randomly into one of four treatments according to sex and BW (seven replications with five pigs per pen). The treatment groups consisted of 4 diets with omega-6:omega-3 FA ratios of 17:1, 15:1, 10:1, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…Our findings are in accordance with those of Nguyen et al, 2020 [66], who reported that using different n-6 to n-3 FAs ratios in diets based on corn-soybean meal seemed to have no effect on gas emission in growing pigs. We presume that the type of diet and the concentration of EFAs may influence how much E-CH 4 is reduced.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are in accordance with those of Nguyen et al, 2020 [66], who reported that using different n-6 to n-3 FAs ratios in diets based on corn-soybean meal seemed to have no effect on gas emission in growing pigs. We presume that the type of diet and the concentration of EFAs may influence how much E-CH 4 is reduced.…”
Section: Discussionsupporting
confidence: 93%